PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 011 PONDOK GELUGUR KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Samuali, Samuali; Witri, Gustimal; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve learning outcomes IPA Elementary School fifth grade students cottage gelugur 011 Lubuk Batu Jaya subdistrict Indragiri Hulu using learning model Quantum Teaching in the academic year 2014/2015. This study is a Class Action Research (Classroom Actions Research), which consists of four stages: planning, action, observation, and reflection. Subjects in this study were students of class V SDN Pondok 011 gelugur totaling 26 students consisting of 17 boys and 9 girls. Based on the results of research and data analysis known that an increase in the percentage of teachers activity gained only 85.93% success rate with excellent qualifications (SB) and the activity students acquire 75.78% success rate with good qualifications (B). It is necessary to improve in the second cycle. While in the second cycle there was an increase in the implementation of research actions on the second cycle than the cycle I. In the teacher activity increased with 92.96% success rate and success of student activity by 89.84%. In addition, improving student learning outcomes before applied learning models Quantum Teaching is 61.67. At UH 1 first cycle to 74.72 which have increased as much as 21.16%, the number of students who completed 11 students. In the second cycle increased the average value of as much as 18.58% to 88.61. All students completed the implementation of the UH 2 (100%). It can be concluded that the model of Quantum Teaching learning can improve learning outcomes IPA Elementary School fifth grade students cottage gelugur 011 Lubuk Batu Jaya subdistrict Indragiri Hulu.Keywords : Quantum Learning Model of Teaching , Learning Outcomes IPA